PENGARUH TATA KELOLA PROSES PEMBELAJARAN TERHADAP KEPUASAN PESERTA PELATIHAN TEKNIS PENYULUH INDUSTRI DAN PERDAGANGAN DI BALAI DIKLAT INDUSTRI REGIONAL V SURABAYA - Sonang Sitohang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
The objective of this study is to investigate the simultaneous and partial effect of Executed Learning Process consist of; Instructor Competency, Curriculum, Library Facility, Learning Media, Laboratory, Training Scheduling, Administration Service, and Program Evaluation on Satisfaction of Training Participants Technical Extension Industrial and Trade on Industrial Training Office Region V Surabaya. The sample of this study consist of 139 Functional Extension Staffs, the training participants in the period of 2003 – 2007. The study uses population research method (Arikunto:1998). Data Estimated is using Multiple Linear Regression Model.The empirical result of study by simultaneous F-test shows that Instructor Competency, Curriculum, Library Facility, Learning Media, Laboratory, Training Scheduling, Administration Service, and Program Evaluation influence on satisfaction of Technical Training Participants on Industrial Training Office Region V Surabaya. The result by partial t-test shows that Instructor Competency, Learning Media not influence satisfaction, but another factors such as; Curriculum, Library Facility, Laboratory, Training Scheduling, Administration Service, and Program Evaluation influence on Satisfaction of Training Participants Technical Extension Industrial and Trade on Industrial Training Office Region V Surabaya .